ROA and CR's Impact on Stock Prices in IDX Main Dealers (2017-2020): Dampak ROA dan CR terhadap Harga Saham pada Perusahaan Perbankan di IDX Main Dealers (2017-2020) - Riza Almaidah; Nihlatul Qudus Sukma Nirwana (Academia Open, 2022)
This study investigates the relationship between Return On Assets (ROA), Current Ratio (CR), and Stock Prices for Bank Companies listed in the Main Dealers of the Indonesia Stock Exchange (IDX) during the period 2017-2020. The research employs purposive sampling to select the sample, and Multiple Linear Regression as the data analysis method. The findings reveal that ROA significantly influences Stock Prices in Bank Companies listed in the IDX Main Dealers during the specified period, while CR also exerts a significant impact on Stock Prices. This research contributes to the existing literature by providing empirical evidence of the relationship between financial ratios and stock market valuation for the banking sector. The implications of these findings highlight the importance of profitability (ROA) and liquidity (CR) in influencing the stock market performance of bank companies, thereby aiding investors, analysts, and policymakers in making informed decisions regarding investment and regulatory measures in the banking industry. Highlights: Financial ratios (ROA and CR) have a significant impact on stock prices. Bank companies listed in the IDX Main Dealers are influenced by ROA and CR. The study provides empirical evidence and insights for the banking sector (2017-2020). Keywords: ROA, CR, Stock Prices, Bank Companies, IDX Main Dealers